Targeting the Mammalian Target of Rapamycin for Epileptic Encephalopathies and Malformations of Cortical Development - Jeong, Anna (J Child Neurol, 2017)
Malformations of cortical development represent a common cause of epileptic encephalopathies and drug-resistant epilepsy in children. As current treatments are often ineffective, new therapeutic targets are needed for epileptic encephalopathies associated with cortical malformations. The mechanistic/mammalian target of rapamycin (mTOR) pathway constitutes a signaling pathway that drives cellular and molecular mechanisms of epileptogenesis in a variety of focal cortical malformations. mTOR inhibitors prevent epilepsy and associated pathogenic mechanisms of epileptogenesis in mouse models of tuberous sclerosis complex and are currently in clinical trials for drug-resistant seizures in these patients. A recent explosion of genetic studies has linked mutations in various genes regulating the mTOR pathway to other cortical malformations, such as focal cortical dysplasia and hemimegalencephaly. Thus, mTOR inhibitors represent promising candidates as novel antiseizure and antiepileptogenic therapies for epilepsy associated with a spectrum of cortical malformations.